Pengembalian Kerugian Keuangan Negara yang Dilakukan Secara Tidak Sukarela Berdasarkan Undang-Undang No. 31 Tahun 1999 Jo. Undang-Undang No. 20 Tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi (Studi Kasus Putusan Mahkamah Agung No. 2257 K/PID/2006 (Lex Jurnalica, 2009)
Corruption is act criminal to take state belonging asset so ability loss state its to perform liabilities and takes on answer him in mensejahterakan society. As consequence it corruption begets rights loss society base rights for prosperous. In this paper about problem which will be worked through is why financial disadvantaged return state have to play a part that momentous enforcement criminal acts corruption and how financial disadvantaged return mechanism state which done by ala not voluntary. In arrange this paper, Writer does normatif's research or bibliography research bases primary law material, secondary jurisdictional material and material jurisdictional tertiary. Meanwhile theory those are used in this paper, Writer utilizes Theory of criminal by use of Absolute Theory, Relative theory, and Affiliate Theory, and Asset Return Theory. There is result even of this research shows that financial disadvantaged return state has to play a part that momentous because will impacted direct for gets to recover state finance or state economics and financial loss return state constitutes enforcement system sentences good pidana's ala and civil. meanwhile financial disadvantaged return mechanism state which did by not voluntary by use of two instrument sentence which is instrument criminal and civil instruments. There is tips even Writer in this paper is Statute Corruption ought to manage more about corruption result asset those are on abroad, so will evoke handicap in term their execution and Government has transparent in money management usufructs corruption that paidr goes to exchequer and get widely been laided at the door to public.Keywords:Â  Corruption, Disadvantages State, Corruption remove